Prospects for the observation of Primordial Black Hole evaporation with the Southern Wide field of view Gamma-ray Observatory. Issue 8 (19th August 2021) - López-Coto, R.; Doro, M.; de Angelis, A.; Mariotti, M.; Harding, J.P.
Abstract: Primordial Black Holes (PBHs) are remnants of objects formed in the early Universe. Their lifetime is an increasing function of their mass, so PBHs in the right mass range can end their lives in an evaporation event that is potentially detectable by our instruments now. This evaporation may result in a γ-ray flash that can be detected by the current generation of Very-High-Energy γ-ray detectors. The Southern Wide field of view Gamma-ray Observatory (SWGO) will be part of the next generation of these instruments. It will be able to establish limits on PBH evaporations for integration windows between 0.5 and 5 s, in a radius of 0.25 pc around the Earth, being sensitive to a rate of the order of ∼50 pc -3 yr -1, more than one order of magnitude more constraining than the currently established best limits.